Si APIK Application Training as an Application for Accountability of Financial Reports for Ahlul Qur'an Islamic Boarding Schools in South Sumatra - Chandra Satria (Jurnal Pengabdian Pancasila (JPP), 2023)
This community service is carried out with the aim of providing solutions for managing financial accountability at the Ahlul Qur'an Islamic Boarding School in South Sumatra. The manual recording that has been carried out so far by the pondok management does not describe efficient financial performance because it only looks at the amount of incoming funds connected with the outgoing funds of the pondok and an overview of the remaining funds available. So that the expected more information on the financial performance of Islamic boarding schools cannot be optimized. This community service activity will be held on Saturday April 29, 2023 from 08.00 to 12.00 WIB.. The material presented in the training is in the form of a basic introduction and understanding of accounting equations as a provision for initial knowledge to get to know basic accounting and any accounts. which are known and then transaction practices in cases from January to March 2023. The result of the training for this activity is the understanding of participants knowing and making financial accountability for Islamic boarding school business activities in the form of financial reports using the SI Apik Bank Indonesia application.